Analysis of Lead (Pb) Contamination in Lipstick and Eye Shadow Powder in the King Street Market in Bandar Lampung Using UV-Visible Spectrophotometer Method - Alya Pinahayu Sakanthi; Syaikhul Aziz; Salsa Nabila Ahlika Ulya; Auli, Winni (Indonesian Journal of Chemical Science, 2024)
Lipsticks and eye shadows are cosmetics frequently used by women every day. Some cosmetic products contain heavy metals like lead. This study aims to validate the UV-Visible Spectrophotometer method for analyzing lead in cosmetics and determine the lead content in lipsticks and eye shadows. Sample preparation was conducted using closed wet digestion with reflux. The samples consisted of 5 lipsticks and eye shadows from the King Street Market in Bandar Lampung. Lead content was determined using a UV-Visible spectrophotometer after method validation. Validation parameters included selectivity, linearity (correlation coefficient = 0.998), accuracy (% recovery = 99-100%), precision (%RSD = < 2% for all experiments), detection limit 0.044 µg/mL, and quantitation limit 0.148 µg/mL, all of which met validity criteria. Lead levels in lipsticks ranged from ±6,000 to 11,000 µg/gram, while in eye shadows, they ranged from ±5,000 to 10,000 µg/gram. The results indicate that lead levels in lipsticks and eye shadows exceed the BPOM RI limit of 20 µg/gram.